(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Transgenic resistance to insects has been shown in plants expressing insecticidal genes such as δ-endotoxins from Bacillus thuringiensis (Bt), protease inhibitors, enzymes, secondary plant metabolites, and plant lectins. While transgenic plants with imported Bt genes have been implemented in many crops on a worldwide basis, the alternative genes have received much less attention. The protease inhibitor and lectin genes primarily influence insect growth and development and, in most cases, do not result in insect death. The effective concentrations of these proteins are considerably higher than the Bt toxin proteins. Therefore, the potential of some of the alternative genes can only be realized by deploying them in conjunction with traditional host plant resistance and Bt genes. Genes giving resistance to insects may also be distributed as multilines or synthetic varieties. Initial indications from deployment of transgenics with insect resistance in various cropping systems in USA, Canada, Argentina, China, India, Australia, and South Africa indicate that single transgene products in conventional cultivar back- grounds are not a formula for sustainable pest control. Instead, a far more complicated strategy may be required, one which may entail deployment of a mixture of various transgenes in diverse backgrounds. Under varied climatic circumstances and agricultural systems of tropics, the success in the use of transgenics for pest control may require decentralized national breeding pro- grams and numerous small-scale seed businesses. While many trans- genic crops containing insecticidal genes have been introduced in the temperate areas, relatively little has been done to utilize this technology for enhancing agricultural yield in the harsh conditions of the tropics, where the need for increasing food supply is most urgent. There is a need to establish suitable methods for deployment of transgenics for pest control, bearing in mind the pest spectrum involved, and the impacts on nontarget species in the environment.